Evaluating Strategies for Adaptation to Climate Change in Grapevine Production–A Systematic Review - Naulleau, Audrey; Gary, Christian; Prévot, Laurent; Hossard, Laure (Frontiers in Plant Science, 2021)
In many areas of the world, maintaining grapevine production will require adaptation to climate change. While rigorous evaluations of adaptation strategies provide valuable lessons to decision-makers, those that are published often overlook major constraints, ignore local adaptive capacity, and suffer from a compartmentalization of disciplines and scales. The objective of our study was to gather evaluation studies in order to identify current knowledge of evaluation methods and their limitations. We reviewed 110 papers that evaluate adaptation strategies in the main vineyards worldwide. Evaluation approaches are analyzed through key features (e.g. climate data sources, methodology, evaluation criteria) to discuss their ability to address climate change issues, and to identify promising outcomes for climate change adaptations. We highlight the fact that combining adaptation levers in the short and long term (location, vine training, irrigation, soil and canopy management, etc.) enables local compromises to be reached between future water availability and grapevine productivity. The main findings of the paper are threefold: (1) the evaluation of a combination of adaptation strategies provides better solutions for adapting to climate change; (2) multi-scale studies allow local constraints and opportunities to be considered; and (3) only a small number of studies have developed multi-scale and multi-lever approaches in order to quantify feasibility and effectiveness of adaptation. In addition, we found that climate data sources were not systematically clearly presented, and that climate uncertainty was hardly accounted for. Moreover, only a small number of studies have assessed the economic impacts of adaptation, especially at farm scale. We conclude that the development of methodologies to evaluate adaptation strategies, considering both complementary adaptations and scales, is essential so as to propose relevant information to the decision-makers of the wine industry.